PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (STUDI PADA KARYAWAN HOTEL MUTIARA MERDEKA PEKANBARU) - Yuliyanti Fransiska Br. Sitompul; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to analyze the organizational culture and work environt and its employee jobsatisfaction.. organizational culture as a variable (X1), work environtas a variable (X2), and employee jobsatisfaction as a variable (Y). The method in this research is descriptive and quantitative using SPSS 16, wherein the samples used are employees of the is 95 done by census and data collection through questionnaires. The results of the analysis using the validity, reliability, determination test, simple linear regression, multiple linear regression test, t test and F. It can be concluded that the organizational culture have a significant effect on employee jobsatifaction of the hotel mutiara merdeka ,pekanbaru work environt significantly influence employee jobsatisfaction of thehotel mutiara merdeka pekanbaru and organizational culture and, work environt significant employee jobsatisfaction the hotel mutiara merdeka pekanbaru.Keywords:, Organizational culture , work environt and Employee jobsatisfaction